PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT KHUSUS IBU DAN ANAK PKU MUHAMMADIYAH KOTAGEDE YOGYAKARTA - Yuliantoharinugroho Yuliantoharinugroho; Rini Pujianti (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
This study aims to analyze consumer satisfaction at PKU Muhammadiyah Kotagede Yogyakarta. This study uses service quality variables consisting of tangible, reliability, responsiveness, assurance, empathy as independent variables to analyze their effect on customer satisfaction as the dependent variable. The population in this study were outpatients who had received services at the PKU Muhammadiyah Kotagede Special Hospital for Mothers and Children, Yogyakarta, with a total of 130 respondents. The sampling technique in this study was using the Simple Random Sampling technique with a sample of 98 samples. The data analysis technique in this study used Multiple Linear Regression analysis which was processed with the SPSS 17.0 program. The results showed that there was an effect of tangibles (physical evidence) on patient satisfaction, which was indicated by tcount of 2,459. There is an effect of empathy (empathy) on patient satisfaction as indicated by the t-value of 3.275. There is an effect of reliability (reliability) on patient satisfaction as indicated by the t-value of 2.603. There is no effect of responsiveness (responsiveness) on patient satisfaction as indicated by the t-value of 1.614. There is no influence of the assurance variable (guarantee) on patient satisfaction as indicated by the t-value of 0.151. The results of the F test (ANOVA) prove that the quality of service, which is tangible, reliability, responsiveness, assurance, and empathy, has a simultaneous effect on customer satisfaction, which is indicated by the value of Fcount = 17,248 , the value is greater than F table which is 2,313, and the 0.000 significance level is smaller than 0.05. The service quality variable that is empathetic has the most dominant influence on consumer satisfaction.